Analysis of hygrothermal conditions for laying hens in the state of Oaxaca - Rosario Díaz, Ángel; Alavéz Ramírez, Rafael; Caballero Caballero, Magdaleno; Chiñas Castillo, Fernando; Montes Bernabé, José Luis; Silva Rivera, María Eugenia (Revista Mexicana de Ciencias Agrícolas, 2018)
For the passive design and location of a poultry farm it is necessary to know the thermal regime of the environment and that of the laying hens. The extreme conditions can cause death due to heat stress to the birds as well as a significant drop in production. The objective of this work was to elaborate the statistical analysis of the polygon of hour comfort of laying hens based on the temperature and humidity index (ITH), for the 9 bioclimates in the state of Oaxaca. Initially, bibliographic data were collected to determine the thermal comfort zone and the optimal ITH. Subsequently, it was determined that the ranges proposed by all the authors are met for a better production with the comfort temperature values for the hens, in the range between 18 °C -22 °C and relative humidity between 60% - 70%. Then, an hourly analysis of the hygrothermal conditions in which the bird is found was carried out by calculating the hourly ITH. The results show that laying hens have an emergency hygrothermal condition and danger during the year in the following proportion: warm bioclimate 20.14% in emergency condition and 32.99% in dangerous condition; humid warm bioclimate 4.86% in emergency condition and 38.54% in dangerous condition; warm dry bioclimate in 1.74% in emergency condition and 18.75% in dangerous condition.